An architecture for enabling IoT interoperability between cross-platforms. (31st August 2021) - Konduru, Venkateswara Raju; Bharamagoudra, Manjula R.
The internet of things (IoT) continues to evolve and more and more IoT platforms provide access to things. However, IoT's ability lies in the development of cross-domain IoT ecosystems in these platforms, offering new, unexpected applications and value-added services. We have identified two key perspectives critical to the development of an IoT ecosystem: 1) enable interoperability between platform development and cross-platform implementation of applications on internet platforms; 2) market (or trade centre) to exchange and adapt IoT resources. Given these two important perspectives of an IoT ecosystem, this article introduces the bridging the interoperability gap (BIG) IoT architecture as the basis for the creation of IoT ecosystems. Architecture responds to key needs that have been evaluated by industry and research associations as a key aspect of the BIG IoT project. We present a proof of the application of the concept in the context of a smart healthcare scenario. We adopted the generic RESTful application programming interface (API) methodology to detect and interact the smart object platforms.